The Production of Vegetable Oil-Based Polyols and Modelling of Rheological Properties - Aydoğmuş, Ercan; Gür, Müge (Turkish Chemical Society, 2017)
In this study, some vegetable-oil based polyols were produced from the different vegetables oils with the catalysts. The produced polyols compared with commercial polyols in terms of rheological properties such as viscosity, temperature, shear stress, shear rate. The rheological properties of the polyols were modelling with general equations based on experimental data. Canola, cotton, linseed, corn, hazelnut and soybean oils were used in the production of polyols. The polyol production was accomplished by oxygen bonding to the structure followed by hydroxyl bonding by breaking the double bonds in the oil. These steps were, respectively, the steps of epoxidation, hydroxylation and purification. In this study, variations of viscosities of soybean oil, cottonseed oil, corn oil, hazelnut oil, canola oil, linseed oil-based polyols and commercial polyols were determined a function of temperature. It is known that the viscosity of the fluid decreases as temperature increases. The tested polyols showed Newtonian and non- Newtonian fluids behavior at certain temperature range. According to the experimental data; the linear and non-linear regression were made to determine coefficients of regression in the model equations.
Keywords: Engineering; Mühendislik